Estimating Carbondioxide Emission and Mitigation Strategies from Land Use and Land Cover Change in Banyuwangi - Wahyuni, Nurlita Indah; Soemarno, Soemarno; Hasyim, Abdul Wahid (Jurnal Pembangunan dan Alam Lestari, 2025)
The land use and land cover change phenomenon has brought social and economic benefits such as agricultural land expansion, which increases food production for a rapidly growing population. On the other hand, it has also been reported to impact terrestrial ecosystem change and its service, including climate change control. The study aimed to estimate CO2 emission from land use and land cover change in Banyuwangi during 1995–2019 and formulate mitigation options to reduce CO2 emission. Four satellite images from 1995, 2000, 2014, and 2019 were used to classify land use and cover and then investigate the changes. This study applies a historical-based approach to estimate emissions to project future emissions using REDD Abacus SP software. There are 12 land use and land cover based on supervised classification: primary forest, secondary forest, plantation forest, mangrove forest, plantation, settlement, cropland, paddy field, shrubs, water, fishpond, and barren land. The land use and land cover change during the period 1995 to 2019 increased both CO2 emissions and sequestration. From 1995 to 2019, land use and land cover change in Banyuwangi emitted 1,5 million tons of CO2-eq/yr and sequestered 0,5 million tons of CO2-eq/yr. Under Business as Usual (BAU) or without mitigation effort, the emission will decrease to 1,2 million tons CO2-eq/yr in 2030. The implementation of the Regional Spatial Plan (RSP) prepared by the Banyuwangi Regency Government is projected to reduce emissions by 47.59% of net emissions from emission without mitigation. If the RSP scenario is added with efforts to prevent deforestation, net emissions can be reduced by 89.21%. Implementing Banyuwangi RSP can become best practice mitigation because it prioritizes the balance of protected areas and cultivation and maintains economic growth. Keywords: banyuwangi, carbon dioxide, emission, land cover, land use, mitigation